Antimicrobial use in animal farms in Egypt: rates, patterns, and determinants - Nada ElSayed; Amira Amine; Laila El-Attar; Mohamed E. K. Amin (Journal of the Egyptian Public Health Association)
Abstract Background While antimicrobial use (AMU) in human healthcare has received significant attention as a key driver of antimicrobial resistance (AMR), less emphasis has been placed on AMU practices and attitudes in animal husbandry. To address this gap, this study examines the patterns and underlying drivers of AMU on animal farms. Methods A survey instrument was distributed to farm staff in 150 animal farms across 15 Egyptian governorates. Farms were selected from a list curated by a private platform specialized in Egypt’s poultry and cattle industry. An online search was conducted to identify additional farms not included in the list or when the contact information was unavailable. The instrument covered key items related to AMU including types of antimicrobials used, indications, their perceived benefits, and the feed conversion ratio (FCR). Using the theory of reasoned action (TRA) as a guiding theoretical framework, this study assesses key factors influencing the AMU behavior of farm personnel. Results Out of 150 farm personnel invited to fill out the survey forms, 111 (74%) responded and agreed to participate. All surveyed personnel reported using antimicrobials, and almost two-thirds (65%) reported using them for non-therapeutic purposes. Non-therapeutic use of antimicrobials, however, had no impact on FCR across all farm types (poultry, cattle, and mixed). The most used antimicrobials were penicillins (81%), followed by macrolides (78%) and tetracyclines (72%). Half of the studied farms reported using colistin, with more than half of this segment (55%) reporting using it for non-therapeutic purposes. Farm personnel’s AMU behavior was associated with the TRA constructs: perceived benefits of antimicrobials (attitude) and perceived AMU behavior in other farms (subjective norm). Conclusions Antimicrobials are unanimously used in animal farms in Egypt, including those classified as last-resort options, such as colistin. Using antimicrobials for disease prevention or growth promotion did not decrease the FCR. Interventions that target the farm personnel’s attitude and the subjective norm should be carried out to change their behavior regarding the use of antimicrobials. Egyptian guidelines for AMU in livestock are urgently needed, along with training to raise awareness of AMR and safer practices. The use of last-resort drugs like colistin should be banned in animal farming, and national surveillance systems should monitor AMU and AMR trends.